Apomictic Malus plants exhibit abnormal pollen development - Liu, Dan-Dan; Wang, Da-Ru; Yang, Xuan-Yu; Zhao, Chang-Hui; Li, Shao-Hua; Sha, Guang-Li; Zhang, Rui-Fen; Ge, Hong-Juan; Tong, Xian-Song; You, Chun-Xiang (Frontiers in Plant Science, 2023)
Apomixis is the asexual reproduction through seeds that leads to the production of genetically uniform progeny. It has become an important tool in plant breeding because it facilitates the retention of genotypes with desirable traits and allows seeds to be obtained directly from mother plants. Apomixis is rare in most economically important crops, but it occurs in some Malus species. Here, the apomictic characteristics of Malus were examined using four apomictic and two sexually reproducing Malus plants. Results from transcriptome analysis showed that plant hormone signal transduction was the main factor affecting apomictic reproductive development. Four of the apomictic Malus plants examined were triploid, and pollen was either absent or present in very low densities in the stamen. Variation in the presence of pollen was associated with variation in the apomictic percentage; specifically, pollen was absent in the stamens of tea crabapple plants with the highest apomictic percentage. Furthermore, pollen mother cells failed to progress normally into meiosis and pollen mitosis, a trait mostly observed in apomictic Malus plants. The expression levels of meiosis-related genes were upregulated in apomictic plants. Our findings indicate that our simple method of detecting pollen abortion could be used to identify apple plants that are capable of apomictic reproduction.